Peningkatan Daya Saing Bank Sampah melalui Inovasi Produk dan Pemasaran Digital Berkelanjutan - Hidayati, Aprihatiningrum; Rofi, M. Akhsanur (PERWIRA - Jurnal Pendidikan Kewirausahaan Indonesia, 2025)
This study aims to enhance the capacity and competitiveness of urban waste banks through product innovation and sustainable digital marketing, incorporating a social entrepreneurship approach. The intervention, involving two waste bank partners in Jakarta—Bank Sampah Puspa Cindra Kana and Bank Sampah Gunung Emas—included training on product design using plastic waste, digital marketing strategies, and fostering an entrepreneurial mindset for sustainable business management. Results show significant improvements in partners' ability to produce high-value recycled products, such as recycle boards, and expand markets through social media and e-commerce. Post-training analysis revealed a notable increase in sales and competitiveness, along with a stronger entrepreneurial understanding. The program’s implications include strengthening the social entrepreneurship capacity of the partners, enabling them to manage the business independently, sustainably, and innovatively. In conclusion, the training program positively impacted waste bank sustainability and community welfare, while empowering waste banks as social entrepreneurs in urban settings.